Plasma depletions lasting into daytime during the recovery phase of a geomagnetic storm in May 2017: Analysis and simulation of GPS total electron content observations. Issue 5 (22nd October 2021) - Otsuka, Yuichi; Shinbori, Atsuki; Sori, Takuya; Tsugawa, Takuya; Nishioka, Michi; Huba, Joseph D.
Abstract: This paper reports that plasma density depletions appearing at middle latitudes near sunrise survived until afternoon on 29 May 2017 during the recovery phase of a geomagnetic storm. By analyzing GPS data collected in Japan, we investigate temporal variations in the horizontal two‐dimensional distribution of total electron content (TEC) during the geomagnetic storm. The SYM‐ H index reached −142 nT around 08 UT on 28 May 2017. TEC depletions extending up to approximately 38°N along the meridional direction appeared over Japan around 05 LT (LT = UT + 9 hours) on 29 May 2017, when TEC rapidly increased at sunrise due to the solar extreme ultraviolet (EUV) radiation. The TEC depletions appeared sequentially over Japan for approximately 8 hours in sunlit conditions. At 06 LT on 29 May, when the plasma depletions first appeared over Japan, the background TEC was enhanced to approximately 17 TECU, and then decreased to approximately 80% of the TEC typical of magnetically quiet conditions. We conclude that this temporal variation of background plasma density in the ionosphere was responsible for the persistence of these plasma depletions for so long in daytime. By using the Naval Research Laboratory: Sami2 is Another Model of the Ionosphere (SAMI2), we have evaluated how plasma production and ambipolar diffusion along the magnetic field may affect the rate of plasma depletion disappearance. Simulation shows that the plasma density increases at the time of plasma depletion appearance; subsequent decreases in the plasma density appear to be responsible for the long‐lasting persistence of plasma depletions during daytime. The plasma density depletion in the top side ionosphere is not filled by the plasma generated by the solar EUV productions because plasma production occurs mainly at the bottom side of the ionosphere. Key Points: Plasma density depletions appearing over Japan near sunrise on 29 May 2017 survived until the afternoon during the recovery phase of a geomagnetic storm. The initial enhancement of the TEC at sunrise, followed by a reduction in TEC, could be responsible for the long‐lasting persistence of plasma depletions during daytime. The plasma density depletion in the topside ionosphere is not filled by the plasma generated by solar EUV photoionization for several hours.